Assessment of Personality Traits Influencing the Performance of Men in Team Sports in Terms of the Big Five - Piepiora, Paweł (Frontiers in Psychology, 2021)
The purpose of this article is to define the perspective from which a coach should analyze and evaluate personality traits that influence sports performance in team sports. The subjects of the research are Polish players (N = 300) in senior age (20–29 years) from 10 team sports (each n = 30). A sample of champions (n = 13) was selected from the study population, and the Big Five model was applied to examine their personality with the use of the NEO Five-Factor Inventory questionnaire. Statistical analyses were performed with the IBM SPSS Statistics software, version 25. The study revealed statistically significant differences between team sports in four personality traits: neuroticism, extraversion, agreeableness, and conscientiousness. Champions of team sports were characterized by a lower level of neuroticism, a higher level of extraversion, and openness to experiences in relation to other sportsmen. It was also confirmed that the personality traits distribution levels depend on the sport discipline. Therefore, an important role must be assigned to those mental training techniques that favor emotional balance, team communication, and tactical thinking skills and are manifested in triggering start-up readiness.